2018
DOI: 10.1080/07853890.2018.1468922
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers in saliva and serum of patients with rheumatoid arthritis with respect to periodontal status

Abstract: Elevated serum concentrations of MMP-8 and IL-6 in CRA patients reflected chronic RA, while elevated salivary concentrations of MMP-8 levels in ERA patients reflected increased periodontal inflammation. Key messages Concentrations of inflammatory biomarkers in serum and saliva were different between patients with RA and healthy controls. Concentrations of MMP-8 and of IL-6 in serum were elevated in patients with chronic RA reflecting joint inflammation and the burden of established RA. Concentrations of MMP-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…In the current study, salivary IL‐6 concentrations were elevated in the DWP group compared with the DWoP group but less dramatically than demonstrated by Costa et al This may be explained by the fact that Costa et al’s periodontitis group appeared to have more severe oral disease, fewer teeth and higher HbA1C levels than our DWP group. Thus, the severity of periodontitis and poor T2DM disease control may relate to higher salivary IL‐6 concentrations, which is consistent with our prior findings that salivary IL‐6 concentrations correlated with serum concentrations and that select salivary biomarkers are influenced by systemic inflammation (Ayravainen et al, 2018; Dekker et al, 2017; Miller et al, 2014; Mirrielees et al, 2010). Our findings suggest that IL‐6 may have limited utility, with its primary usefulness within the context of a targeted panel of salivary biomarkers for periodontitis.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, salivary IL‐6 concentrations were elevated in the DWP group compared with the DWoP group but less dramatically than demonstrated by Costa et al This may be explained by the fact that Costa et al’s periodontitis group appeared to have more severe oral disease, fewer teeth and higher HbA1C levels than our DWP group. Thus, the severity of periodontitis and poor T2DM disease control may relate to higher salivary IL‐6 concentrations, which is consistent with our prior findings that salivary IL‐6 concentrations correlated with serum concentrations and that select salivary biomarkers are influenced by systemic inflammation (Ayravainen et al, 2018; Dekker et al, 2017; Miller et al, 2014; Mirrielees et al, 2010). Our findings suggest that IL‐6 may have limited utility, with its primary usefulness within the context of a targeted panel of salivary biomarkers for periodontitis.…”
Section: Discussionsupporting
confidence: 89%
“…We have recently reported that in this study population, salivary MMP‐8 associated with periodontal parameters (Äyräväinen et al, ). Here we show that salivary MMP‐8 levels were increased already at the beginning of the study in ERA patients probably indicating poor periodontal health, which even got worse in the monotherapy group during the follow‐up.…”
Section: Discussionmentioning
confidence: 59%
“…So far salivary biomarkers have been found to play profound role in diagnosis of many diseases or stressful conditions including cancers (Arantes et al, 2018; Kaur et al, 2018; Khurshid et al, 2018), liver diseases (Abe et al, 2018; Morán and Cubero, 2018), kidney diseases (Maciejczyk et al, 2018b), neurological (Farah et al, 2018) and cardiovascular diseases (Gohel et al, 2018), psoriasis (Asa'ad et al, 2018), systemic lupus erythematosus (Stanescu et al, 2018), and rheumatoid arthritis (Äyräväinen et al, 2018). In one of the very recent review, it has been enumerated that majority of the biomarkers in saliva have diagnostic potential for neoplasms, followed by detection of metabolic disorders and least for systemic disorders (Mortha et al, 2018).…”
Section: Stress Biomarkers In Salivamentioning
confidence: 99%